The role of faculty members in promoting digital citizenship for their students: Umm Al-Qura University as a model - Amani Qalyobi (Umm Al-Qura University, 2022)
The aim of the current research is to identify the reality of the practice of the faculty members at Umm Al-Qura University for their role in promoting digital citizenship from the students' point of view. (Respect - Education - Protection), on a stratified random sample of regular undergraduate students which consisted of (520) students. For the three domains combined, the domain of (Education) came in the first order of the domains of reinforcement with a very high degree, followed by the domain of (Protection) with a high degree, and in the third arrangement the domain of (Respect) with a medium degree. and also, there is no differences in the degree of estimation of the research sample to the reality of the role of faculty members in promoting citizenship due to the variable (gender), while there were statistically significant differences according to the variable (specialization) in favor of practical colleges, and there were differences according to the variable (Academic level) in favor of the level Fifth grade or higher. The researcher recommended, the need to formulate strategies related to achieving digital citizenship in universities and the mechanisms for their implementation, and the roles and responsibilities of the elements of the university system in the implementation processes.